2020
DOI: 10.3390/molecules25184089
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Activity and ROS Regulation Effect of Sinapaldehyde in LPS-Stimulated RAW 264.7 Macrophages

Abstract: We evaluated the anti-inflammatory effects of SNAH in lipopolysaccharide (LPS)-stimulated RAW 264.7 macrophages by performing nitric oxide (NO) assays, cytokine enzyme-linked immunosorbent assays, Western blotting, and real-time reverse transcription-polymerase chain reaction analysis. SNAH inhibited the production of NO (nitric oxide), reactive oxygen species (ROS), tumor necrosis factor (TNF)-α, and interleukin (IL)-6. Additionally, 100 μM SNAH significantly inhibited total NO and ROS inhibitory activity by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 58 publications
4
38
0
Order By: Relevance
“…The effect of Lfd-NPs on the expression of tumor necrosis factor alpha (TNF-α) and Interleukin (IL)-6 in the supernatant of LPS-treated THP-1 human monocytes and RAW 264.7 murine macrophage cells was investigated via an enzyme-linked immunosorbent assay (ELISA) ( Figure 6 ). TNF-α has been linked to a variety of signaling processes inside cells that result in necrosis or apoptosis [ 58 ], while IL-6 is known to contribute to an acute phase immune response via inducing the synthesis of acute phase proteins such as CRP [ 59 ]. As shown in Figure 6 , in cultures of LPS-treated cells, both TNF-α and IL-6 concentrations were significantly increased, compared to untreated control cells ( Figure 6 A–D).…”
Section: Resultsmentioning
confidence: 99%
“…The effect of Lfd-NPs on the expression of tumor necrosis factor alpha (TNF-α) and Interleukin (IL)-6 in the supernatant of LPS-treated THP-1 human monocytes and RAW 264.7 murine macrophage cells was investigated via an enzyme-linked immunosorbent assay (ELISA) ( Figure 6 ). TNF-α has been linked to a variety of signaling processes inside cells that result in necrosis or apoptosis [ 58 ], while IL-6 is known to contribute to an acute phase immune response via inducing the synthesis of acute phase proteins such as CRP [ 59 ]. As shown in Figure 6 , in cultures of LPS-treated cells, both TNF-α and IL-6 concentrations were significantly increased, compared to untreated control cells ( Figure 6 A–D).…”
Section: Resultsmentioning
confidence: 99%
“…ROS signaling is also essential for the activation of inflammasomes, molecular platforms playing a key role in the processing of pro-inflammatory cytokines, such as IL-1β, IL-18, and IL-33 ( Harijith et al., 2014 ; Pham and Park 2020 ). Unsurprisingly, ROS inhibitors may ameliorate the inflammatory conditions triggered by diverse stimuli and prevent the development and progression of inflammation-linked complications ( Yang et al., 2018 ; Baek et al., 2020 ). In line with previous reports, we observed that blockade of ROS signaling by either suppressing NOX-mediated ROS production with DPI or scavenging ROS using NAC leads to decreased COX-2 expression in macrophages, confirming the involvement of ROS in modulating COX-2 in our experimental models.…”
Section: Discussionmentioning
confidence: 99%
“…The NO contents and ROS levels in the supernatants were determined after centrifugation at 1000 rpm for 5 min and incubation for 24 h by measuring the fluorescence intensity at 485 nm and 540 nm, according to the instructions. Then, the NO contents and ROS levels were calculated according to standard curve and formula (1), respectively [ 49 ]. The cell fluorescence images were analyzed using a Nikon fluorescence microscope (ECLIPSE NI, Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%